The Development of Wireless Power Transfer Technologies for Low Power Applications: An Acoustic Based Approach - Saat, S.; Mokhtar, N.F.; Zaid, T.; A. Ghani, Z.; M. Isa, A. A.; Darsono, A.M.; Yusop, Y.; A.Rahman, F.K.; Husin, S.H.; M. Isa, M.S.; M. Zin, M.S.I. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2015)
Wireless power transfer (WPT) is the transmission of electrical power across a medium without the use of electrical conductors. This paper aims to transfer low power wirelessly by using acoustic based method. The feasibility of transmitting electric power through some specific surface or material by propagating acoustic waves using piezoelectric transducers was analyzed here. The efficiency of power transmission for Acoustic power transfer (APT) has been briefly examined for different transmission medium. For this paper, the air and metal block were chosen as the transfer medium and the efficiency performance of these medium have successfully been analyzed. At the end, a prototype of APT system was developed which was capable of transferring voltage through air at the maximum distance of 10cm at 0.96V. The prototype of APT system with metal medium had also been completed but it failed to transmit the power due to unsuitability of transducer used.